BILINGUALISM AND EDUCATION OF CHILDREN IN A BILINGUAL FAMILY - Jana Kadaníková; Karel Neubauer (Listy klinicke logopedie, 2017)
The essay is devoted to the problematic of bilingualism and approach to the child upbringing in bilingual family environment. The accepted knowledge devoted to the problematic is resumed, together with the content of the term 'bilingualism', the particular kinds of bilingualism are approached as well as the characteristics of bilinguists speech manifestation and approach to bilingual parenting style. The qualitative research consists of two targeted case studies of children growing up in bilingual families and their qualitative analysis. The summary of implications targeted to the field of speech-language pathologist profession with bilingual child is a part of the essay's conclusion.